Influence of Internet Marketing Strategies on the Market Share of Online Shops in Nairobi County in Kenya - Orare , Gregory; Nkirina , Severina (Journal of Marketing Studies, 2019)
Purpose: The online shopping sector in Kenya is still not well developed and online commercial activities contribute to just over 1% of Kenya's GDP. Kenya's rate of online shopping is 23% and currently lags behind the global rate of online shopping which is 59%. The different level of development in online shopping between Kenya and other developed economies shows that the sector still has a long way to go in Kenya. Online shops face competition from the conventional "˜brick-and-mortar' stores and supermarkets. In order to deal with the competition most online shops market their products using internet marketing, which is defined as advertising of a company's products or services over the internet with the view of increasing profits or market share. Market share is the percentage of an industry acquired by a company during a certain period of time. This study aimed to establish the influence of internet marketing strategies on the market share of online shops in Kenya. The specific objectives of the study were: to determine the influence of website design strategies on the market share of online shops in Nairobi County in Kenya; to establish the influence of content marketing strategies on the market share of online shops in Nairobi County in Kenya; to assess the influence of affiliate marketing strategies on the market share of online shops in Nairobi County in Kenya and to establish the influence of social media marketing strategies on the market share of online shops in Nairobi County in Kenya. Methodology: This study adopted descriptive research design. The study covered 68 respondents drawn from a population of 34 online shops operating within Nairobi County, with an average of 2 respondents selected per organization. The study relied on data collected using a questionnaire comprising of both open-ended and close-ended questions, structured to meet the objectives of the study. The data was analyzed using inferential statistics by means of Statistical Packages for Social Sciences version 20. Results: The results indicated a P-value of 0.0002, which is less than 0.05 against all the variables in the study. This indicated that website design marketing strategies, content marketing strategies, affiliate marketing strategies and social media marketing strategies had a significant influence on the market share of online shops in Nairobi County. The study revealed a positive correlation between website design and market share with a correlation coefficient of 0.015, a positive correlation between content marketing and market share with a correlation coefficient of 0.163, a positive correlation between affiliate marketing and market share with a correlation coefficient of 0.057, and a positive correlation between social media marketing and market share with a correlation coefficient of 0.923. The study concluded that social media marketing strategies contributed the most to the overall market share of online shops in Nairobi, followed by content marketing strategies, affiliate marketing strategies and finally website design marketing strategies. Unique Contribution to Theory and Practice: The study recommended that online shops needed to come up with an internet marketing mix that incorporated all the different strategies given that the respondents gave varied views on which internet marketing strategies were more influential. The County governments were encouraged to look into ways of making internet connectivity more affordable since most online shops indicated unreliable and expensive internet as a challenge when trying to conduct internet marketing. The "˜brick-and-mortar' shops that were not making a profit were also urged to consider the online business model. Retail customers were advised to be willing to accept change and embrace online shopping. Keywords: Website design strategies Content marketing strategies, Affiliate marketing strategies, Social media marketing strategies and Market share.